Diagnosis of Woolly Hair Using Trichoscopy - Mahesh Mathur; Prakash Acharya; Alina Karki; Nisha KC; Jyoti Shah (Hindawi Limited, 2019)
Hair shaft abnormalities including woolly hair are traditionally diagnosed by clinical examination and light microscopy which involves plucking of multiple hairs for examination. This is usually an inconvenient procedure especially in children. Trichoscopy may be a useful tool allowing close visualization of multiple hairs without causing discomfort to the patients. Trichoscopic findings of woolly hair have been described only in few reports. We report all of the trichoscopic findings of this rare disorder in one case which have only been reported separately in previous reports.